Pneumococcal carriage and disease amongst children from the United Kingdom and Nepal - Kandasamy, R (2017)
Pneumococcal disease continues to be responsible for an extraordinary amount of human death and disability around the world. In particular, the burden of disease weighs greatest upon those children who reside in low and low-middle income countries of the world. It must also be recognised however, that the continued emergence of disease due to pneumococcal serotypes not covered by pneumococcal conjugate vaccines, due to serotype replacement, is an unfolding issue which is increasingly impacting upon the health of children in middle and high income countries. In the short and medium term work needs to be focused on achieving the greatest benefits from the intelligent use of currently available pneumococcal conjugate vaccines. Whilst the long term vision towards combating pneumococcal disease needs to focus on better understanding the underlying biology, particularly through the use of contemporary technologies. As an insight into the above mentioned issues faced by resource-rich countries, this thesis aims to describe the dynamics of pneumococcal carriage and disease in the United Kingdom following the introduction of the thirteen-valent pneumococcal conjugate vaccine (PCV13) to the infant immunisation schedule. From the perspective of a resource limited setting, this thesis also aims to utilise the population of pneumococci collected from amongst Nepalese children prior to PCV introduction to; determine the pneumococcal serotype distribution, determine the utility of a molecular diagnostic tool for identifying pneumococcal pneumonia, determine the molecular epidemiology of pneumococci in this population, and determine the antibiotic resistance patterns of pneumococci in this population. Finally, with the intention of exploring the overall diversity of pneumococcus and how this may be influenced by PCV introduction, this thesis aims to also describe the global population structure of pneumococci prior to PCV introduction. Key findings of this thesis include; the differential effect of PCV13 on serotypes 3 and 19A, and the rise of non-vaccine type disease amongst children from the United Kingdom, the characterisation of carriage prior to PCV10 introduction and the high rate of multiple serotype carriage amongst Nepalese children, the identification of host immune and antibiotic selective pressures on pneumococcal surface protein A (pspA), pneumococcal surface protein C (pspC), and penicillin binding proteins, the almost unchecked rise of antimicrobial resistance amongst pneumococci in Nepal, and the description of the global pneumococcal population prior to PCV introduction, which shows that some strains have characteristics which facilitate spread across geographic regions. These findings highlight the need for further studies investigating how PCVs could be better applied in United Kingdom infants and children in order to try and minimise the observed differential effects. The identification of the pneumococcal surface proteins which are under selective pressure (pspA and pspC) highlights these proteins as promising antigens for inclusion in a novel vaccine that would provide an avenue for preventing pneumococcal disease using a non-serotype specific approach. The resistance patterns of pneumococci in Nepal indicate that further steps both from a surveillance and policy stand point need to be taken to monitor and curb pneumococcal antimicrobial resistance in Nepal. Finally, it is clear that ongoing surveillance of pneumococcal carriage and disease is needed both in the United Kingdom and Nepal. Of most interest will be the post-PCV effect on the pneumococcal population in Nepal.